PENGARUH PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. PEMBANGUNAN PERUMAHAN Tbk CABANG KALIMANTAN DI BALIKPAPAN - bayu indra siswanto (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
Effect implementation of occupational health and safety on employee productivity at PT. Pembangunan Perumahan Tbk Branch Kalimantan in Balikpapan, under the guidance of Drs. M. Zaini and Mr. Eko A. Widyanto, SE., M.SA. The results showed that simultaneous independent variables consist of occupational safety (X1) and occupational health (X2) significantly affects employee productivity dependent variable (Y). Partially of occupational safety (X1) had no significant effect on employee productivity (Y) and partially of occupational health (X2) have a significant effect on employee productivity (Y). From these results obtained by the coefficient of determinantion (R Square) of 0536, this matter showed that independent variable that is occupational safety (X1) and occupational health (X2) appreciable effected to employee productivity of 53,6%, while the remaining of 46,4% effected by variables which was not examined in this research.